Narrowing the skills gap for innovation - Dias, Casimiro (2014)
Background: The current financial crisis and the increasing burden of chronic diseases are challenging hospitals to enhance their innovation capacity to deliver new and more effective health services. However, the shortage of skills has been widely recognized as a key obstacle for innovation. Ensuring the presence of a skilled workforce has become a priority for the health system in Portugal and across Europe. Objective: The aim of this study was to examine the demand of new skills and their influence in both investments in innovation and development of skills. Methods: We used a mixed-methods approach combining statistical analysis of data survey and content analysis of semistructured interviews with the Administration Boards of hospitals, using a nominal group technique. Results: The results illustrate an increasing demand of a broad range of skills for innovation development, including responsibility and quality consciousness (with a significant increase of 55%, 52/95), adaptation skills (with an increase of 44%, 42/95) and cooperation and communication skills (with an increase of 55%, 52/95). Investments in the development of skills for innovation are mainly focused on aligning professional training with an organizational strategy (69%, 66/95) as well as collaboration in taskforces (61%, 58/95) and cross-department teams (60%, 57/95). However, the dynamics between the supply and demand of skills for innovation are better explained through a broader perspective of organizational changes towards enhancing learning opportunities and engagement of health professionals to boost innovation. Conclusions: The results of this study illustrate that hospitals are unlikely to enhance their innovation capacity if they pursue strategies failing to match the skills needed. Within this context, hospitals with high investments in innovation tend to invest more in skills development. The demand of skills and investments in training are influenced by many other factors, including the hospital's strategies, as well as changes in the work organization. Relevant implications for managers and policy makers can be drawn from the empirical findings of this paper, building on the current efforts from leading innovating hospitals that are already defining the future of health care.